Guidelines for the creation of POP Reporting or Integrated Popular Financial Reporting (European journal of volunteering and community-based projects, 2023)
The Popular Financial Reporting, also known as Bilancio POP, serves as a transparent and simplified form of social reporting designed to facilitate communication between government entities and citizens. This document outlines essential guidelines for constructing the Integrated Popular Reporting (Bilancio POP), catering to both academics and practitioners.Inspired by fundamental criteria and the need for guideline definition, the Bilancio POP adheres to key principles. The document's structure and guidance underscore the integration of the Six Capitals, including intellectual, human, natural, productive, social, and financial capital. Detailed content reflects various perspectives, with basic drafting criteria ensuring clarity.The accountability process and the paradigm shift in communication between government and citizens are explored, emphasizing a dialogical approach and needs delineation. Practical examples illustrate the perimetration of needs, aligning with the smart city concept and technologies supporting reporting.The governance aspects of smart cities, characteristic contents, and the role of networks are addressed. Performance indicators span diverse sectors such as healthcare, natural resources, construction, education, transportation, and quality of life, considering personalized needs and sustainability. The public-private partnership, economic growth, pollution control, waste management, water and air quality, and social impact assessment are integrated into the reporting framework.The document emphasizes the importance of considering all impacts, approval by governing bodies, and third-party certification of the information collection and representation system. Ultimately, the Bilancio POP seeks to provide a concise and easily comprehensible overview of public administration activities, catering to a broad audience, including citizens, politicians, public sector employees, media, and community groups.
Keywords: Popular Financial Reporting; Integrated Popular Reporting; POP Accounting; Smart City; Social Reporting; Audit